2018
DOI: 10.5935/abc.20180168
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness Use for Early Monitoring of Cardiovascular Adverse Events due to Anthracycline Chemotherapy in Breast Cancer Patients. A Pilot Study

Abstract: BackgroundChemotherapy with doxorubicin and cyclophosphamide, although efficient for treating breast cancer, is associated with cardiovascular complications. Recent studies seek to identify methods that can early detect cardiological and vascular changes as a strategy to decrease the incidence of cardiovascular comorbidities.ObjectiveTo evaluate the role of arterial stiffness measurement in the monitoring of doxorubicin and cyclophosphamide-induced cardiotoxicity in breast cancer patients.MethodsProspective lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
(70 reference statements)
1
7
0
2
Order By: Relevance
“…Unlike these previous studies, we found that clinical cardiovascular hemodynamic risk factors such as central and brachial blood pressure, as well as PWV and Pb in both groups, did not change after the chemotherapy, which implies that in the short term, both AC-T and CAF chemotherapy did not appear to exert acute adverse hemodynamic risks ( Table 2 ). Similar to our findings, Souza et al reported that the hemodynamic parameters associated with arterial stiffness were not changed in the early phase of doxorubicin-based chemotherapy [ 52 ]. The discrepancy between our findings and several previous reports may be due to the relatively younger enrolled participants (mean age: 44 years) in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Unlike these previous studies, we found that clinical cardiovascular hemodynamic risk factors such as central and brachial blood pressure, as well as PWV and Pb in both groups, did not change after the chemotherapy, which implies that in the short term, both AC-T and CAF chemotherapy did not appear to exert acute adverse hemodynamic risks ( Table 2 ). Similar to our findings, Souza et al reported that the hemodynamic parameters associated with arterial stiffness were not changed in the early phase of doxorubicin-based chemotherapy [ 52 ]. The discrepancy between our findings and several previous reports may be due to the relatively younger enrolled participants (mean age: 44 years) in this study.…”
Section: Discussionsupporting
confidence: 92%
“…However, DOX causes acute and chronic toxic adverse effects that are dosage dependent, and cardiotoxicity is a potentially fatal toxic side effect [48,49]. Moreover, arterial stiffness is induced in patients undergoing chemotherapy with DOX, serving as a monitor of cardiovascular events [50]. DOX causes cardiovascular damage through inducing cardiomyocyte death pathways, including autophagy, ferroptosis, pyroptosis, and apoptosis [51].…”
Section: Ligustrazine (Chuan Xiong Qin) Activates 14-3-3γ To Reduce C...mentioning
confidence: 99%
“…Moreover, anthracycline-related vascular impairment may occur as a result of chemotherapy side effects 74,75 . For example, adult survivors of breast cancer present increased pulse wave velocities that represent aortic and/or arterial stiffness after anthracycline or trastuzumab chemotherapy [76][77][78] . Increased arterial stiffness is associated with the development of cardiovascular events including atrial fibrillation 79 and stroke 80 in non-cancer populations.…”
Section: Pulse Wave Analysismentioning
confidence: 99%